2016
DOI: 10.1016/j.kint.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis for the treatment of kidney diseases

Abstract: The purpose of this review is to examine the evidence supporting the application of plasma exchange in renal disease. Our review focuses on the following 6 most common renal indications for plasma exchange based on 2014 registry data from the Canadian Apheresis Group: (i) thrombotic thrombocytopenic purpura (TTP)/hemolytic uremic syndrome; (ii) renal transplantation, (iii) antineutrophil cytoplasm antibodies-associated vasculitis, (iv) cryoglobulinemia, (v) focal segmental glomerulosclerosis, and (vi) Goodpast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 127 publications
(179 reference statements)
0
26
0
4
Order By: Relevance
“…Therapy should address the underlying cause of CV, and consists mainly of antiviral drugs for HCV, immunosuppressive agents for lymphoproliferative disorders and autoimmune diseases. TPE has been employed since the 1980s as adjunctive therapy in organ or life‐threatening CV manifestations, such as glomerulonephritis, severe refractory cutaneous vasculitis and hyperviscosity syndrome (Berkman & Orlin, ; Evans et al , ; Clark et al , ). The largest multicentre cohort study reported a significant beneficial effect in almost 50% of cases, while improvement of baseline condition was partial in 25% and insufficient in 22% of cases (Marson et al , ).…”
Section: Tpe In Non‐haematological Autoimmune Disordersmentioning
confidence: 99%
“…Therapy should address the underlying cause of CV, and consists mainly of antiviral drugs for HCV, immunosuppressive agents for lymphoproliferative disorders and autoimmune diseases. TPE has been employed since the 1980s as adjunctive therapy in organ or life‐threatening CV manifestations, such as glomerulonephritis, severe refractory cutaneous vasculitis and hyperviscosity syndrome (Berkman & Orlin, ; Evans et al , ; Clark et al , ). The largest multicentre cohort study reported a significant beneficial effect in almost 50% of cases, while improvement of baseline condition was partial in 25% and insufficient in 22% of cases (Marson et al , ).…”
Section: Tpe In Non‐haematological Autoimmune Disordersmentioning
confidence: 99%
“…The kidneys are the target organ in a wide variety of autoimmune diseases, particularly such as systemic lupus erythematosus (lupus nephritis), Goodpasture's syndrome, purpura Henoch-Schönlein, Wegener's granulomatosis, polyarteritis nodosa, in which vasculitis is an important component of the pathogenesis. And application of a plasma exchange is here too justified [24,25].…”
Section: Kidney Damage In Vasculitismentioning
confidence: 99%
“…Historically, plasmapheresis was first applied to humans in 1952 to treat hyperviscosity in multiple myeloma [1]. The first plasmapheresis in kidney diseases was attempted by Bukowski et al [2]; they successfully treated two patients with thrombotic thrombocytopenic purpura (TTP) and renal impairment in 1977.…”
Section: Introductionmentioning
confidence: 99%